PELATIHAN TEKNIK PEMASANGAN DAN PERAWATAN KAMERA CCTV UNTUK GURU DAN LABORAN DI SMK KOTA BEKASI - Muhammad Yusro; Aodah Diamah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract The development of legal regulations with the enactment of Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE) has accommodated electronic evidence including closed circuit television (CCTV) recordings which can be used as evidence in court. In many educational institutions/agencies such as schools/madrasas/campuses, many CCTVs are installed to monitor the situation inside the classroom, outside the classroom and around the school. The phenomenon of the widespread installation of CCTV cameras in schools makes it important to have CCTV installation, maintenance and repair skills for teachers, technicians or school laboratory assistants. In addition, CCTV skills can also be taught to students of the electronics engineering expertise program as part of the additional technical expertise that vocational students need to have. The method of implementing Community Service is in the form of online (online) training by providing CCTV installation and maintenance training to teachers/laborers/technicians located at SMKN 2 Bekasi City. The number of participants who attended were 27 people according to the set target. All participants take part full-time in each training session and contribute to discussions via zoom meetings. The evaluation results show that after participating in this training the participants are able to use electronic measuring instruments, install at least 1 CCTV and understand the technicalities of maintaining and repairing CCTV. Abstrak Perkembangan regulasi hukum dengan berlakunya UU No.11 tahun 2008 tentang Informasi dan Transaksi Elektronik (UU ITE) telah mengakomodasi alat bukti elektronik termasuk diantaranya hasil rekaman Closed Circuit Television (CCTV) yang dapat dijadikan sebagai alat bukti di persidangan. Di banyak instansi/lembaga pendidikan seperti sekolah/madrasah/kampus, CCTV banyak dipasang untuk memantau situasi di dalam kelas, di luar kelas maupun di sekitar sekolah. Fenomena maraknya pemasangan kamera CCTV di sekolah menjadikan keterampilan pemasangan, perawatan dan perbaikan CCTV penting dimiliki oleh guru, teknisi atau laboran sekolah. Selain itu keterampilan tentang CCTV dapat pula diajarkan kepada para siswa program keahlian teknik elektronika sebagai bagian keahlian teknik tambahan yang perlu dimiliki oleh siswa SMK. Metode pelaksanaan Pengabdian kepada Masyarakat berupa pelatihan online (daring) dengan memberikan pelatihan pemasangan dan perawatan CCTV kepada guru/laboran/teknisi yang bertempat SMKN 2 Kota Bekasi. Jumlah peserta yang hadir sebanyak 27 orang sesuai target yang ditetapkan. Seluruh peserta mengikuti penuh waktu setiap sesi pelatihan dan memberikan kontribusi dalam diskusi via zoom meeting. Hasil evaluasi menunjukkan bahwa setelah mengikuti pelatihan ini peserta mampu menggunakan alat ukur elektronika, memasang minimal 1 buah CCTV dan memahami teknis merawat dan memperbaiki CCTV.